Three-dimensional oscillating flow between two parallel plates through a porous medium - Guria, M.; Ghara, N.; Jana, R.N. (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady Couette flow between two parallel plates when upper plates oscillates in its own plane and is subjected to a constant suction and the lower plate to a injection velocity distribution through the porous medium has been analyzed. The approximate solution has been obtained using perturbation technique. It is seen that the primary velocity increases whereas the secondary velocity decreases with an increase in permeability parameter.
Keywords: Couette flow; three-dimensional; injection; suction; transverse sinusoidal